Nilai-Nilai Pendidikan Akhlak Dalam Film Animasi Hafiz Dan Hafizah Episode Serakah Jadi Masalah (Bagian 1-2) - Erwina, Meifa Adinda; Kustati, Martin; Gusmirawati; Amelia, Rezki (STAI Tebing Tinggi Deli, 2024)
The aim of this research is to evaluate the moral education values ​​found in the animated episode Hafiz and Hafizah with the episode Greedy Becomes a Problem (parts 1-2). This film tells the story of how the two main characters, Hafiz and Hafizah, face moral challenges because of their greed. The method used is a qualitative method using content analysis research. Data was collected by watching films and reading literature about moral values ​​in education. The results of research into the moral education values ​​found in the animated film Hafiza and Hafizah are the value of mahmudah (praiseworthy) moral education and the mazmumah (despicable) moral education value. The value of mahmudah (praise) moral education is found in part 1, including: helping, maintaining cleanliness. Mazmumah (reprehensible) morals include: fighting among friends, feeling lazy. Meanwhile, the educational value of mahmudah (praiseworthy) morals is found in part 2, including: apologizing, caring for fellow friends, giving advice for goodness, mazmumah (despicable) morals, including: haste, selfishness, greed, slander. This film also provides a relevant moral message for children and emphasizes the negative effects of greed. It is hoped that this research can increase awareness and develop moral education materials through animated film media.